Accountability, Assessment, and the Literacies of Information and Communication Technologies - Asselin, Marlene; Early, Margaret; Filipenko, Margot (Canadian Journal of Education/Revue canadienne de l'éducation, 2005)
In this article, we have explored the issues that Ministries of Education confront in their large‐scale assessment policies and practices as literacy curricula expand to include the new literacies of information and communication technologies. Based on a series of interviews with Ministry personnel, we have described their current progress to include the new literacies, plans for the future, and the dilemmas and challenges in considering the demands of new times. We argue for a more balanced approach to assessment and accountability, one that recognizes the limitations of current public accountability measures and situates them within a broader assessment framework. Key words: large scale assessment, Canadian assessment practices, policy, testing, new literacies Dans cet article, les auteures étudient les enjeux auxquels sont confrontés les ministères de l’Éducation dans leurs politiques et méthodes en matière d’épreuves communes au fil de l’intégration des technologies de l’information et de la communication au sein des programmes de litératie. À partir d’une série d’entrevues réalisées auprès de fonctionnaires de ces ministères, les auteures font le point sur l’inclusion des nouvelles littératies, la planification du développement envisagé, les dilemmes et les défis qu’impliquent les exigences actuelles. Elles préconisent une approche plus équilibrée de l’évaluation et de l’imputabilité, laquelle tiendrait compte des limites des mécanismes d’imputabilité actuels et les situerait dans un cadre d’évaluation plus vaste. Mots clés : tests communs, méthodes d’évaluation canadiennes, politiques, nouvelles littératies.